Determining the Minimum Age of Marriage in the Perspective of Economics and Al-Ikhtiyath Al-Fiqhy - Lathoif Ghozali, Muhammad; Yudha, Ana Toni Roby Candra; Himami, Fatikul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this study is to find out and provide views on the determination of the minimum age of marriage from two perspectives, namely the economic perspective and the economic perspective al Ikhtiyath al fiqhy. The method used in this study is qualitative, juridical-normative approach, as well as descriptive qualitative because the data needed and used are in the form of information leaflets that do not need to be quantified. The study found that the findings of previous research on young marriage were confirmed in this study. It found that young marriage is known to increase the risk of miscarriage, infant mortality, cervical cancer, venereal disease, and mental disorders due to social pressure to assume adult responsibilities at a young age. This is a prohibition that must be avoided and is very contrary to Islamic rules la dharara wa la dhirar. These rules are taken to realize the objectives of the maqashid al-syariah by rejecting the ones that mafsadah, by eliminating the harm or at least alleviating it. The corresponding suggestion is to encourage education as early as possible for adolescents so that they know the bad things that have the potential to arise if they force early marriage. Two things that are very important for adolescents to have but scientifically and empirically are considered immature are age and mental preparation. So, it is necessary to pay serious attention to these two things before deciding to marry their couple.